2016
DOI: 10.1074/jbc.m116.737601
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Affinity Differentially Influences Protein Kinase C Regulation and Inhibitor Potency

Abstract: The overlapping network of kinase-substrate interactions provides exquisite specificity in cell signaling pathways, but also presents challenges to our ability to understand the mechanistic basis of biological processes. Efforts to dissect kinase-substrate interactions have been particularly limited by their inherently transient nature. Here, we use a library of FRET sensors to monitor these transient complexes, specifically examining weak interactions between the catalytic domain of protein kinase C␣ and 14 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…One intriguing explanation is that the regulatory-catalytic domain interaction, which is significantly stronger in the presence of nucleotide, physically prevents phosphatases from accessing the phosphorylation sites on the catalytic domain. Finally, we recently observed that both PKC and PKA show positive cooperativity between substrate and ATP binding to the catalytic domain (34), which highlights a potentially conserved mechanism that drives catalytic-regulatory domain interactions.…”
Section: Table 2 Steady-state K D Measurementsmentioning
confidence: 91%
“…One intriguing explanation is that the regulatory-catalytic domain interaction, which is significantly stronger in the presence of nucleotide, physically prevents phosphatases from accessing the phosphorylation sites on the catalytic domain. Finally, we recently observed that both PKC and PKA show positive cooperativity between substrate and ATP binding to the catalytic domain (34), which highlights a potentially conserved mechanism that drives catalytic-regulatory domain interactions.…”
Section: Table 2 Steady-state K D Measurementsmentioning
confidence: 91%
“…We recently demonstrated that BimI, a staurosporine derivative, inhibits binding of both ATP and substrate peptides to the PKC α catalytic domain. 9 In this work, FRET measurements of a range of nucleotide and staurosporine analogues reveal a systematic correlation between inhibitor structure and substrate displacement. Combining FRET measurements with MD simulation analysis, we uncover an allosteric switch region located outside the ATP binding site.…”
mentioning
confidence: 82%
“…8,9 We have previously demonstrated that the potent ATP-competitive PKC inhibitor BimI displaces substrate binding to the catalytic domain of PKC α . 9 To test a potential intersection between BimI and the allosteric switch mechanism involving K347−D481, we used MD simulations to examine the conformational dynamics of PKC α in the presence of BimI. The amine group at the end of the n -propyl chain of BimI makes a salt bridge with D481 to disrupt the D481−K347 interaction (Figure 2A).…”
Section: Role Of K347 and D481 In The Design Of Inhibitors With Bitopmentioning
confidence: 99%
See 1 more Smart Citation
“…that their interaction could be transient, as in the case of many other similar interactions involving a kinase and its substrate (Sommese and Sivaramakrishnan, 2016). Next, we tested if TSC1 is a direct substrate for IKKε by performing an in vitro kinase assay ( Figure 4C).…”
Section: Tsc1 Directly Interacts With Ikbke and Is Phosphorylated By mentioning
confidence: 99%